Mammographic Breast Density Response to Aromatase Inhibition - Vachon, Celine M. (2013)
PURPOSE: Mammographic breast density (MBD) is decreased by tamoxifen, but the effect of aromatase inhibitors (AI) is less clear. EXPERIMENTAL DESIGN: We enrolled early stage postmenopausal breast cancer patients initiating adjuvant AI therapy and ascertained mammograms before and at an average 10 months of AI therapy. We matched cases to healthy postmenopausal women (controls) from a large mammography screening cohort on age, baseline body mass index, baseline MBD and interval between mammograms. We estimated change in MBD using a computer-assisted thresholding program (Cumulus) and compared differences between cases and matched controls. RESULTS: In predominantly white women (96%), we found 14% of the 387 eligible cases had a MBD reduction of at least 5% after an average of 10 months of AI therapy. MBD reductions were associated with higher baseline MBD, AI use for more than 12 months and prior postmenopausal hormone use. Comparing each case to her matched control, there was no evidence of an association of change in MBD with AI therapy (median case-control difference among 369 pairs was −0.1% (10(th) and 90(th) percentile: −5.9%, 5.2%) p=0.51). Case-control differences were similar by type of AI (p’s 0.41 and 0.56); prior use of postmenopausal hormones (p=0.85); baseline MBD (p=0.55); or length of AI therapy (p=0.08). CONCLUSIONS: In postmenopausal women treated with AIs, 14% of cases had a MBD reduction of >5%, but these decreases did not differ from matched controls. These data suggest that MBD is not a clinically useful biomarker for predicting the value of AI therapy in white postmenopausal women.